3D-Printed Boron-Nitrogen Doped Carbon Electrodes for Sustainable Wastewater Treatment via MPECVD - Kaczmarzyk, Iwona; Szopińska, Malgorzata; Sokołowski, Patryk; Sabbatini, Simona; Strugala, Gabriel; Ryl, Jacek; Barucca, Gianni; Falås, Per; Bogdanowicz, Robert; Pierpaoli, Mattia (Nano-Micro Letters, 2025)
This study proposes a novel and sustainable method for fabricating 3D-printed carbon-based electrodes for electrochemical wastewater treatment. We prepared B,N-doped carbon electrodes with hierarchical porosity and a significantly enhanced surface area-to-volume ratio (up to 180%) compared to non-optimized analogues using a synergistic combination of 3D printing, phase inversion, and microwave plasma-enhanced chemical vapor deposition. This process allows the metal-free growth of vertically aligned carbon nanostructures directly onto polymer-derived substrates, resulting in a 20-fold increase in the electrochemically active surface area. Computational fluid dynamics simulations were used to improve mass transport and reduce pressure drop. Electrochemical characterization demonstrated that the optimized electrodes performed significantly better, achieving 4.7-, 4-, and 6.5-fold increases in the degradation rates of atenolol, metoprolol, and propranolol, respectively, during electrochemical oxidation. These results highlight the efficacy of the integrated fabrication and simulation approach in producing high-performance electrodes for sustainable wastewater treatment applications. Highlights: 1 A novel approach combining 3D printing, phase inversion, and microwave plasma-enhanced chemical vapor deposition is presented. This technique enables the creation of carbon-based electrodes with precise micro- and nanoscale control, offering potential for sustainable and high-performance wastewater treatment applications. 2 The synthesized 3D carbon scaffolds, enriched with B,N-doped carbon nanostructures, demonstrated superior performance in the electrochemical oxidation of β-blockers. Computational fluid dynamics simulations were used to optimize electrode design, leading to improved mass transport and reaction kinetics. 3 This research provides a sustainable and scalable solution for removing emerging contaminants from wastewater. The catalyst-free approach simplifies the fabrication process and reduces potential material contamination, making it a promising technology for advanced water treatment applications.